Penciptaan Lukisan Kaligrafi Khat Tsulust di Kayu Halaban - Muhammad Ikhsan; Agus Priyatno (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2026)
Abstract. This creation was inspired by kaidah calligraphy, an art form created by Muslim artists to express religious values through paintings that combine diverse colors with a seemingly free artistic style while still conveying meaningful messages. This work employs verses from Surah Al-Adiyat using the Thuluth (Khat Tsuluth) script, painted on halaban wood as the primary medium. The integration of halaban wood with Thuluth calligraphic painting represents an appealing fusion of local cultural heritage and modern artistic expression. This creation aims to examine the visualization process and the techniques applied in producing calligraphic paintings on halaban wood. The study adopts the Pre-factum, Practice-Led Research method, consisting of four stages: the Preparation Stage, Elaboration Stage, Contemplation Stage, and Artwork Realization Stage. The outcome of this creative process is a collection of 12 calligraphic paintings on halaban wood. The artworks were created using acrylic paint with the opaque (blocking) painting technique. These calligraphic paintings on halaban wood are expected to contribute to cultural preservation by helping the public recognize, appreciate, and preserve cultural heritage through the integration of halaban wood into the art of Islamic calligraphy.